Sense of coherence and coping with the disease in patients with a diagnosis of lung cancer - Kurowska, Krystyna; Weilandt, Katarzyna (Nursing Problems / Problemy Pielęgniarstwa, 2010)
Introduction. One of the important factors in managing cancer is sense of coherence (SOC). The concept of Aaron Antonovsy’s known as salutogenic model assumes that every person is in possession of their own resources to cope with disease. It is the level of SOC, its components as well as a specific model of stress management that determine the way each patient functions in this difficult life situation. Aim of the study. The aim of the study was to assess the level of coherence (and its components) and determine styles of coping with stress in patients with a diagnosis of lung cancer. Material and methods. The study included 76 patients of the of thoracic surgery ward, Oncology Center, Bydgoszcz. Personal questionnaire designed by the authors of the study, Antonovsky’s life orientation questionnaire (SOC–29) and Coping Inventory for Stressful Situations Questionnaire by Szczepanik, Strelau and Wrześniewski (Polish version) were used in the study. Results. The results show that patients with lung cancer have similar levels of SOC and the level of global SOC is lowered. The style they choose most often is the task-oriented style. Conclusions. Estimation of the levels of SOC and social support might be used as determinant of care of patients with cancer at different stages of the disease. Nursing Topics 2010; 1 (1): 11-16